The "Science" of Political Economy – A Victory for Common Sense? A Comparative Reading of Adam Smith and Thomas Reid - Maximilian Priebe (Journal of Contextual Economics – Schmollers Jahrbuch, 2023)
This work offers the first comprehensive comparison between the philosophy of Adam Smith and that of his successor, Thomas Reid. It looks at Reid's and Smith's remarkably similar accounts of human perception and judgement, and at their different moral and economic theories. In this way, this paper offers not only a new perspective on Reid's critique of Adam Smith's Theory of Moral Sentiments, but also new insights into the intellectual roots of the genuinely Scottish debates about sense perception and the task of scientific philosophy. "Reiding" Smith can thus offer a unique vantage point from which to understand the connections between epistemological and economic issues in Smith's work. With a focus that is at once historical and philosophical, this undertaking serves three purposes: a) to familiarise economists with the philosophical and economic works of Thomas Reid, b) to sharpen our understanding of Adam Smith's intellectual context in the Scottish Enlightenment, and c) to better understand the paradoxical role that individual human judgement plays in Adam Smith's analysis of the economy.
Keywords: B12; B31; 330; Thomas Reid; Adam Smith; Scottish Enlightenment; Judgement Gaps; Das Adam Smith Problem; Philosophy of Perception